PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN UNTUK MENINGKATKAN Word of Mouth POSITIF PADA APLIKASI New PLN MOBILE STUDI PELANGGAN PT. PLN (PERSERO) UP3 SEMARANG - Moch Nurfityani; I Made Sukresna (Jurnal Akuntansi dan Pajak, 2023)
Several quality factors that influence customer satisfaction aim to optimize positive Word of Mouth (WoM) including product quality factors and service quality factors. PT. PLN (Persero) itself believes that their growth is also influenced by the level of trust from the community which aims to increase positive Word of Mouth (WoM), therefore PT. PLN (Persero) continues to provide improvements to the quality of their services to the community so that the electricity needs of every home, industry and business can be fulfilled and contribute directly to developing Indonesia. This research can provide recommendations and directions for PT. PLN (PERSERO) UP3 Semarang related to improving the quality of products and services in order to continue to provide good service in order to create regular customer satisfaction. Keywords: Customer satisfaction, word of mouth, product quality